Implementation of Project-Based Learning in English Learning to Improve Students’ Vocabulary Mastery - Rahma, Ghaniyya Wafda (Afeksi: Jurnal Penelitian dan Evaluasi Pendidikan, 2024)
This research was carried out based on the many students facing difficulties in expanding and enriching their vocabulary. Traditional learning approaches that are often used in teaching vocabulary are often monotonous and less attractive to students, which can lead to boredom and helplessness. For this reason, this study aims to improve students' vocabulary mastery skills using Project-Based Learning. This research is a classroom action research conducted in two cycles. The subjects of this study were students in class 7E at SMPN 1 Getasan for the 2022/2023 academic year. The results of the data analysis in this study, that PjBL in learning material part of body and physical appearance can improve students' vocabulary mastery. This can be proven by the increased understanding of students' vocabulary from 5.4% to 81% in the first cycle and 100% in the second cycle. Learning using PjBL also increases the enthusiasm of students with evidence that in making projects students explore their knowledge more and contemplate their understanding with the various media they are interested in.